Nursing errors in the media: patient safety in the window - Elaine Cristina Novatzki Forte; Denise Elvira Pires de Pires; Maria Manuela Ferreira Pereira da Silva Martins; Maria Itayra Coelho de Souza Padilha; Dulcinéia Ghizoni Schneider; Letícia de Lima Trindade
ABSTRACT Objective: To analyze the nursing errors reported by the journalistic media and interpret the main implications of this communication for the visibility of this problem. Method: Documental research, qualitative, descriptive and exploratory, with data collected in news reports from Brazil and Portugal, analyzed through hermeneutics with resources of Atlas Software. Results: We analyzed 112 news items published between 2012 and 2016 that resulted in six categories: Year - highest occurrence in 2012; Age group of the patient - children; Professional category - nurses; Type of error - medication; Outcome - death; Possible attributed cause - occupational conditions. Final considerations: Nursing mistakes are a challenge for the profession, and the way they are communicated by the media is not very explanatory, contributing to a negative visibility of the profession, and to making society insecure. Improving the way they are served in the media contributes to the visibility of the problem without affecting the professional image.